Improving communication skills of beginner BIPA learners through the use of graphic organizers - Asteria, Prima Vidya; Suhartono; Inayatillah, Fafi; Sohnui, Suhailee (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Graphic organizer-based learning media is the right medium to organize ideas in the form of visual concepts so that it can provide a positive contribution to the development of BIPA learners' communication skills. The purpose of this study was to describe the process of implementing the graphic organizer method in learning communication skills in the BIPA beginner class and to describe the results of implementing the graphic organizer method in learning communication skills in the BIPA beginner class. The research method applied was quantitative descriptive with six BIPA students from Surabaya State University as research subjects. The material taught was BIPA SKL with aspects of knowledge of classification words, comparison words, and conjunctions using popular figures in Indonesia as material topics with the following steps: apperception, discussion, provision of material, collaborative project to create a graphic organizer of selected figures with BIPA friends, presentation performance, discussion of errors in the use of classification words, comparison words, and conjunctions, discussion, material reinforcement, closing. In learning activities, BIPA learners showed a positive response with a tendency to actively interact and participate during learning. Learning outcomes showed an average value of 84.16. The most frequently used classification words were "people" and "fruit," while "preferred" and "then" were the most common comparative words. The most used conjunctions were "and," "because," and "so”. The study concluded that graphic organizers can effectively enhance BIPA learners' communication skills by aligning with their learning preferences and providing a structured approach to language learning.